Maintenance Energy Requirements in Modern Broilers Fed Exogenous Enzymes - Caldas, J.V.; Hilton, K.M.; Boonsinchai, N.; Mullenix, G.; England, J.A.; Coon , C.N. (International Journal of Poultry Science, 2022)
Objective: The objective of this study was to determine if exogenous enzymes reduce the metabolizable energy requirements for maintenance in broilers. Materials and Methods: Two feeds were tested, a negative control and negative control plus enzyme composite. The composite was a proprietary blend of glucanase + xylanase + cellulase + arabinofuranosidase + protease + phytase. Feed allowances were 30-100% of the ad libitum feed intake from 16-27 days. The retained energy in the carcass was evaluated as protein gain, g×5.45 kcal g–1+fat gain×8.95 kcal g–1. A linear regression of Y = Retention energy kcal/kg0.70 was regressed by X = Metabolizable energy intake kcal/kg0.70 where the metabolizable energy intake at zero carcass retention energy was the metabolizable energy of maintenance. Results: Body weight gain was +6.39 g day–1 with the enzyme treatment at ad libitum intake. The metabolizable energy for maintenance was 168±4.2 kcal/kg0.70 (R2 = 0.98) for the enzyme treatment and 160±4.5 kcal/kg0.70 (R2 = 0.98) for the control (p<0.01). The efficiency of energy utilization for maintenance and tissue gain was improved by 4 and 3%, respectively with the enzymes. The enzyme had -7.6 kcal/kg0.70 metabolizable energy of maintenance which represents 4.5% lower (p<0.01) than the control. Energy savings from the enzyme composite ranged from 67 kcal kg–1 at ad libitum intake to 238 kcal kg–1 at 30% intake. Conclusion: The present study showed that the enzyme composite reduced the broiler energy requirement for maintenance and improved the efficiency for protein gain. To the authors’ knowledge, this is the first research reporting that an enzyme composite decreases the maintenance energy and changes the tissue efficiency gain. Further investigation is required.